Acculturation and purchase intentions among emigrants: an international analysis - Velgan, Tatiana (2022)
This study investigates the acculturation of Portuguese emigrants in Germany, France and the United Kingdom and the impact of it on their consumer behaviour, in the context of retail. Acculturation is an interchanged culture acquired on emigration into a different culture. It affects the behaviour of migrants as they adjust to the host culture and presents a difficulty for business researchers as they grapple with the consequence of drifts in consumer behaviours, purchasing intentions, cultural attributes, and significant shifts in the desire for certain products. As culture dictates the behaviour to consume things, sways the way people think, perceive, process, and construe information, it is natural to draw some conclusion that it has a significant impact also on businesses bottom line. To examine this, an online questionnaire was conducted to collect data from 2103 respondents from Germany, France, and the United Kingdom. The statistical analysis of the survey data was performed with partial least squares structural equation modelling (PLS-SEM). The results of this study have shown similarities in the acculturation of migrants after a certain duration of their stay, and the marked influence of it on their consumer behaviour in general when compared to that in the literature review. Therefore, the results of the survey indicate that both acculturation and the country of origin affect perceived quality and brand identification. Furthermore, our results evidence the influence of perceived quality and brand identification on consumer purchase intention. Hence, by answering the research question, the results contribute to the body of research on the effects of the country of origin and acculturation among emigrants’ communities.